Pandemic Planning in Homeless Shelters: A Pilot Study of a Coronavirus Disease 2019 (COVID-19) Testing and Support Program to Mitigate the Risk of COVID-19 Outbreaks in Congregate Settings. (8th June 2020) - O'Shea, Timothy; Bodkin, Claire; Mokashi, Vaibhav; Beal, Kerry; Wiwcharuk, Jill; Lennox, Robin; Guenter, Dale; Smieja, Marek; Bulir, David; Chong, Sylvia
Abstract: We tested 104 residents and 141 staff for coronavirus disease 2019 who failed daily symptom screening in homeless shelters in Hamilton, Canada. We detected 1 resident (1%), 7 staff (5%), and 1 case of secondary spread. Shelter restructuring to allow physical distancing, testing, and isolation can decrease outbreaks in shelters.